DIPLOMASI BUDAYA JEPANG MELALUI ANIME DI AMERIKA SERIKAT PADA PERIODE 2016-2019 - Dinda Putri Syafira (2023)
This research explains about Japanese popular culture developed through their cultural product known as anime. This popular culture "anime" already has many fans not only in Japan, but also in the United States. It has even made its way onto American television screens. The Japanese government's initial goal in launching anime was to use it as a cultural diplomacy tool to help promote Japan abroad as a country with a positive image and rich cultural heritage. This research uses the concepts of cultural diplomacy, cool Japan, and nation branding and uses qualitative research methods to assist in its analysis. The results of this study can be concluded that the popularity of anime in the United States has had a wide impact on popular culture in Japan and the United States. The popularity of anime in the United States has the potential to contribute to increased levels of appreciation, understanding, and respect between cultures.